(untitled) (Revista Inclusiones, 2020)
The article analyses the impact of global processes on the activity of ethnic entrepreneurs, as well as the opportunities it creates. With that goal in mind, the conceptual analysis of ethno-economic studies is conducted. The conclusions regarding the development of ethnic businesses are systematized and generalized. The interactive models of the development of ethnic enterprises are created. The strategies used by ethnic entrepreneurs are identified. The dominant trends in the digitalization of the economy are substantiated. Based on that, the mechanism for Russian ethnic entrepreneurs’ participation in the new innovative development trajectory – ethnic trading. Cases of successful ethnic trading are provided